"قيادة الذّات" المفهوم والقياس دراسة سيكومترية على عينة من تلاميذ المرحلة الثّانوية - فرهي, كريمة; بحري, نبيل (University of Eloued جامعة الوادي, 2017)
الدّراسة الحالية مزدوجة الهدف؛ إذ نسعى في شقّ منها إلى استكشاف طبيعة محتوى قيادة الذّات انطلاقا من نظرة شمولية مقترحة، هذه النظرة بنيت على أساس أن قيادة الذّات تتضمن سبعة أبعاد رئيسية تتمثّل في: الشعور بالإنتماء، إستثمار الوقت، التخطيط وتحديد الأهداف، الإتصال الفعّال، فعالية الذّات، التحلي بالقيم الأخلاقية، وقوة الإرادة. ونسعى في شقّها الثاني إلى إعداد مقياس لقيادة الذّات وتقنينه على عينة من تلاميذ المرحلة الثّانوية من الجنسين، وَيَنْبَنِي هذا التنظير وجانبه التطبيقي على توجهين: نسعى في الأول إلى معرفة طبيعة العلاقة الرابطة بين الأبعاد المقترحة والمستوى الكلي لقيادة الذّات، بينما التوجه الثاني يهدف لمعرفة مدى تشبّع فقرات المقياس على الدرجة الكلية، لتكون النتيجة النهائية هي الخروج بمقياس لقيادة الذّات صالح للإستخدام في البيئة المحلية This study has two objectives, The aim is partly to explore the nature of selfleadership from a holistic vision proposed. This vision is based on the principle that self-leadership includes seven major dimensions including: the feeling of belonging, the investment of time, planning and effective communication, self efficiency, moral values and willpower. While in its second phase, it aims to develop a test on Self-leadership and applying it to a sample of high school of both sexes. That said, the application of this dual objective is based on two approaches. The first is to know the nature of the relationship that links the proposed dimensions and the overall level of self-leadership, while the second approach is to determine the degree of saturation of elaborate tests on the final score, so that the end result is achieving a test developed on self-leadership for it to be used in the local environment.
“Self- leadership” concept and measurement Psychometric study on a sample of high school students
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: القيادة، الذّات، الخصائص السيكومترية; leadership, Self, psychometric characteristics